Impact of phase change material-based thermal management on battery thermal safety - Somek, Kutlu; Derun, Emek; Papurello, Davide (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The increasing demand for electric vehicles (EVs) has intensified research on lithium-ion battery safety, particularly regarding thermal runaway (TR) and thermal management systems (TMS). This review battery safety, explores the mechanisms of TR, including mechanical, electrical, and thermal abuse, and highlights strategies for mitigating TR through effective battery thermal management (BTM). Phase change materials (PCMs) have emerged as promising passive thermal solutions due to their latent heat storage capabilities; however, their low thermal conductivity and leakage issues present significant challenges. Recent advancements in composite PCMs, incorporating nanomaterials such as expanded graphite, boron nitride, and metal oxides, have significantly improved heat dissipation and stability. Additionally, active cooling methods, including air, liquid, and thermoelectric systems, are evaluated in hybrid approaches that enhance battery safety and performance. Integrating flame-retardant additives and encapsulated PCMs further improves thermal stability and fire resistance. Artificial intelligence (AI) driven material development strategies are also proposed to optimize PCM formulations and real-time BTM assistance. This review provides a comprehensive analysis of current BTM techniques and future research directions, emphasizing the role of nanotechnology and hybrid cooling methods in enhancing EVs' battery performance, safety, and longevity.
Keywords: Battery safety; Phase change materials; Battery thermal management; Thermal runaway; Nanomaterials; LITHIUM ION BATTERY; ENERGY-STORAGE; RUNAWAY; PERFORMANCE; STABILITY; Thermodynamics; Energy & Fuels; Engineering; Mechanics